2014
DOI: 10.1155/2014/174253
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ultimate pH on Postmortem Myofibrillar Protein Degradation and Meat Quality Characteristics of Chinese Yellow Crossbreed Cattle

Abstract: This paper describes the complex effects of postmortem ultimate pH (pHu) on Chinese Yellow crossbreed cattle quality during postmortem ageing and provides an explanation of how pHu affects beef tenderness. High pHu beef had the highest initial tenderness (P < 0.05) compared with other groups at 1 day postmortem. Intermediate and low pHu beef had similar initial WBSF at 1 day postmortem, but intermediate pHu beef had slower tenderization rate than low pHu beef (P < 0.05). Purge loss, cooking loss, L*, a*, and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 29 publications
(36 reference statements)
2
41
0
6
Order By: Relevance
“…At present, little is known of the effect of Fe on meat quality. pH is a key indicator of meat quality, having a great influence on the quality of chicken carcasses [43,44]. Water holding capacity and meat color are both influenced by pH [45].…”
Section: Discussionmentioning
confidence: 99%
“…At present, little is known of the effect of Fe on meat quality. pH is a key indicator of meat quality, having a great influence on the quality of chicken carcasses [43,44]. Water holding capacity and meat color are both influenced by pH [45].…”
Section: Discussionmentioning
confidence: 99%
“…Figure 7b and c also shows the degradation of desmin (54 kDa) to lower molecular weight of 33.4 kDa protein. This was supported by the report by Li et al (2014), which stated that desmin contributes to the toughness of the meat texture due to its ability to have a significant effect on maintaining the integrity and contractility of muscle cells (Kristensen & Purslow, 2001). In the tenderization technique by Ding et al (2018), degradation of desmin was observed through incubation in µ-calpain and caspase-3 with or without heat shock protein 27 (HSP27).…”
Section: Sds-pagementioning
confidence: 75%
“…The degradation of this protein could destroy the integrity of thin filaments (enlargement of the I-band and lengthening of myofibril sarcomeres) and lead to the breaking of the myofibril. Therefore, by hydrolyzing the troponin T protein, the extent of meat tenderization will be increased (Li et al, 2014;Soltanizadeh, Kadivar, Keramat, & Fazilati, 2008;Zhang et al, 2018). The disappearance of the intact troponin T acted as F I G U R E 7 The electrophoretic analysis of (a) standard ladder protein, (b) control, and (c) after protease treatment an indicator of meat tenderness and has a strong correlation to the shear force (Yan et al, 2018).…”
Section: Sds-pagementioning
confidence: 99%
“…Final pH values, considered as normal for beef cattle meat, are between 5.4 and 5.6. Intermediate pH values are considered above 5.6 and can result in increased water retention and shorter shelf life of the meat compared with pH values considered as normal (Li et al, 2014).…”
Section: Discussionmentioning
confidence: 99%